KEBIJAKAN PENETAPAN PENGELOLAAN TARIF PARKIR BERDASARKAN PERATURAN WALIKOTA PEKANBARU NOMOR 41 TAHUN 2022 TENTANG TARIF LAYANAN PARKIR - Agustiyan, Agustiyan; Junaidi, Junaidi; Akmal, Zainul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
Legislation at the central level gives authority to regions to determineparking levy rates. Pekanbaru city regional regulations set a parking fee of 1000rupiah and in 2022 it will increase to 2000. In 2024 there will be a decrease inparking rates at government-managed traditional markets. Some people protestedagainst the increase in parking rates, which means that the 2022 regulations needto be readjusted so that they can be accepted by the community. The aim of thisresearch is to find out how parking rate management is determined and to find outwhat the ideal form of parking rate management is in the city of Pekanbaru.The type of research used in this research is normative legal research.Data collection techniques include case studies of law journals, books related tothe topic of the problem in the research. From literature study. The data sourcesused are secondary and primary data legal materials. With qualitative dataanalysis, which is a procedure that produces descriptive data.From the results of this research, it can be concluded that the increase inparking rates carried out by the government is purely to increase Pekanbaru cityPAD without paying attention to the sense of justice among the community andoptimizing supervision of the implementation of parking levy collection. Then, inits management, rights and obligations need to be regulated, there also needs tobe facilities and there needs to be accountability from the Pekanbaru citygovernment and it is also necessary to pay attention to the sense of justice in thecommunity.Keywords: Policy, Parking Rates, Management